Mechanisms of cancer-associated thrombosis - Hisada, Yohei; Mackman, Nigel (Research and practice in thrombosis and haemostasis, 2023)
A State-of-the-Art lecture titled “Mechanisms of cancer-associated thrombosis” was presented at the ISTH Congress in 2022. Patients with cancer have a 4-fold to 9-fold increased risk of venous thromboembolism (VTE) compared with the general population, so-called cancer-associated thrombosis (CAT). Different rates of VTE are observed in different types of cancer, suggesting that there are cancer-type specific mechanisms of CAT. We will discuss 4 pathways of CAT: tissue factor, podoplanin, neutrophil extracellular traps, and plasminogen activator inhibitor-1. In addition, specific gene mutations may increase the rate of CAT in some cancer types. A better understanding of these pathways may lead to the identification of biomarkers that can identify patients at risk for VTE and allow the development of new treatments to prevent CAT. Finally, we summarize relevant new data on this topic presented at the 2022 ISTH Congress. •Extracellular vesicle tissue factor and coagulation in cancer-associated thrombosis.•Podoplanin and platelet activation in cancer-associated thrombosis.•Neutrophil extracellular traps and cancer-associated thrombosis.•Plasminogen activator inhibitor-1 and fibrinolysis in cancer-associated thrombosis.